IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH LISTEN-READ-DISCUSS (LRD) STRATEGY AT THE EIGHTH GRADE OF SMP NEGERI 1 LAHEWA IN 2022/2023 - Nazara, Theodora Vinta Sukartini; Zebua, Elwin Piarawan; Harefa, Trisman; Harefa, Afore Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Reading is the process of getting ideas from texts. Reading comprehension meant understanding what had been read and it was an active thinking process that depends. There are several problems faced by students in reading comprehension at the Eighth Grade of SMP Negeri 1 Lahewa, one of which was have problem in comprehending skill in their reading. Therefore, to overcome this, researcher conducted research using the Listen-Read-Discuss strategy. The purpose of the research is to Improving the Students’ Reading Comprehension through Listen-Read-Discussion (LRD) strategy at the Eighth Grade of SMP Negeri 1 Lahewa in 2022/2023. The results of the study were seen from the average score of students from the test evaluation sheet. There are 3 students (10%) included in the failed level, 3 students (10%) included in the less level, 11 students (36%) included in the sufficient level, 4 students (13%) included in good category and 9 students (30%) are included in the very good category. In Cycle II students' abilities increased. There are no students who are categorized as failed and lacking. The highest score is 100 and the lowest score is 75. There is 1 student (3%)